2009
DOI: 10.3354/ame01339
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and trophic role of ciliates and heterotrophic nanoflagellates in Rhone River diluted mesoscale structures (NW Mediterranean Sea)

Abstract: Studies of the Rhone River plume, and in particular its diluted mesoscale structures, have shown over recent years that low salinity water (LSW) is characterised by both high primary and high secondary productivity. Here we compare the structure and grazing activity of the hetorotrophic community (nanoflagellates, ciliates) in the LSW and the surrounding marine water (MW) of the northwestern Mediterranean Sea. Furthermore, we report on the temporal variability of these characteristics all along a Lagrangian tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…A decrease in bacterial production at the surface all along the trajectory (not shown) finally suggests a strong top-down control by ciliates and heterotrophic flagellates on bacteria and small size phytoplankton. Such control mainly exerted by mixotrophs, as shown by Christaki et al (2009), may also explain why a decrease of NO 3 :NH 4 is everywhere observed in the lens and whatever the measured salinity (not shown). Indeed, the top-down control on bacteria and small size phytoplankton may favour the development of large phytoplankton, explaining an important consumption of nitrate along the trajectory.…”
Section: Biogeochemical Analysis Of Bioprhofi Datamentioning
confidence: 75%
See 2 more Smart Citations
“…A decrease in bacterial production at the surface all along the trajectory (not shown) finally suggests a strong top-down control by ciliates and heterotrophic flagellates on bacteria and small size phytoplankton. Such control mainly exerted by mixotrophs, as shown by Christaki et al (2009), may also explain why a decrease of NO 3 :NH 4 is everywhere observed in the lens and whatever the measured salinity (not shown). Indeed, the top-down control on bacteria and small size phytoplankton may favour the development of large phytoplankton, explaining an important consumption of nitrate along the trajectory.…”
Section: Biogeochemical Analysis Of Bioprhofi Datamentioning
confidence: 75%
“…These in situ phytoplankton biomasses can then be compared to the three aforementioned phytoplankton size classes (Phy 1 , Phy 2 , and Phy 3 ) represented by the model. In the same way, an analysis of heterotrophic flagellates and ciliates activity and biomass observed during the cruise is presented by Christaki et al (2009), and integrated biomass of copepods were measured by D. Bonnet (personal communication, 2009), allowing the comparison of zooplankton model outputs (resp. Zoo 1 , Zoo 2 , and Zoo 3 ) with in situ measurements.…”
Section: Biogeochemical Analysis Of Bioprhofi Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, high abundances of picophytoplankton, picoeukaryotes (Liu et al 2004), and nanophytoplankton (Jochem 2003) have been observed in river plumes. Recently, Christaki et al (2009) showed that the PNF abundance was 3 to 5 fold higher in the Rhone River plume waters compared to marine waters. Abundances of PNF and HNF were within the ranges reported in other studies of oligotrophic, mesotrophic, and eutrophic marine ecosystems, mostly from 0.1 to 30 cells ml −1 × 10 3 (Table 4 and references in there).…”
Section: Relative Importance Of Different Nanoflagellate Forms Under mentioning
confidence: 99%
“…4c, 90 % of ciliate biomass). In a recent study in the western Mediterranean Sea, mixotrophs were found to be efficient grazers of nanophytoplankton forming dense populations related to high Chl-a concentrations (Christaki et al, 2009). Tintinnids are also known to form patchy distributions related to their food resources (e.g., Stoecker et al, 1984;Christaki et al, 2008).…”
Section: General and Longitudinal Featuresmentioning
confidence: 99%